Employment Absorption of Vocational High School Graduates in Shipbuilding Expertise Programs in the Oil, Gas, and Shipyard - Irawati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to employment absorption of vocational high school graduates in shipbuilding expertise programs in the oil, gas and shipyards industries. A quantitative descriptive research method was employed. The study was conducted within the shipbuilding expertise program at SMKN 5 Batam and SMKS Teladan Batam. The data sources included graduates of the shipbuilding expertise program from 2020 to 2024, the Career Development Center (CDC) at SMKN 5 Batam, and the public relations office of SMKS Teladan Batam. Data collection techniques involved distributing questionnaires, conducting interviews, and reviewing documentation. Quantitative data analysis was performed using descriptive statistical methods. The research findings indicate that the employment absorption rate of SMK graduates in the shipbuilding expertise program into the oil and gas and shipyard industries in Batam City over the past five years was 6% for the 2020 graduates, 9% for 2021, 16% for 2022, 25% for 2023, and 45% for 2024. Among the various specializations, ship welding was the most highly absorbed into the industries. Most graduates secured employment in the oil and gas and shipyard industries within six months of completing their education. Key sources of job information included the school's CDC, social media, family/relatives, teachers, and acquaintances. Internal factors influencing employment absorption included work experience, soft skills, graduate competencies, and motivation to work in alignment with their expertise. External factors included social networks, the quality of the vocational schools, and the demand for specific job vacancies in the industries. The competencies taught in schools were found to be sufficiently relevant to the current occupations of the graduates.